Identification of Potential Key circRNAs in Aged Mice With Postoperative Delirium - Ran, Wei; Liang, Ning; Yuan, Ruixue; Wang, Zhiqiao; Gao, Jin (Frontiers in Molecular Neuroscience, 2022)
Postoperative delirium (POD) is a common postoperative complication in elderly patients and seriously affects postoperative recovery. The exact mechanism of POD is still unclear. Therefore, it is necessary to explore the mechanism of POD in transcriptional regulation. At present, circRNAs have been proven to play an important role in a variety of mental health and cognitive disorders, such as Alzheimer’s disease, depression and schizophrenia. To reveal the effect of circRNA on POD, we used microarray to analyze the differential expression profiles of circRNAs in the hippocampus of 12-month-old mice between the tibial fracture and control groups. A total of 1,4236 circRNAs were identified. Compared with the control group, there were 500 circRNAs with increased expression and 187 with decreased expression. The accuracy of the microarray data was further verified by qRT–PCR. Finally, GO enrichment and KEGG pathway analyses indicated that changes in axon orientation, ubiquitin-mediated proteolysis, glutamate synapses, the estrogen signaling pathway, the RAS signaling pathway and other systems may be important potential pathological mechanisms in the progression of POD. In particular, we found that the HOMER1 gene and its transcript mmu_circRNA_26701 are specifically expressed in the glutamate synapse, which may provide new clues and intervention targets for the progression of this refractory disease.